2022
DOI: 10.1093/plcell/koac007
|View full text |Cite
|
Sign up to set email alerts
|

A cascade of bHLH-regulated pathways programs maize anther development

Abstract: The spatiotemporal development of somatic tissues of the anther lobe is necessary for successful fertile pollen production. This process is mediated by many transcription factors acting through complex, multi-layered networks. Here, our analysis of functional knockout mutants of interacting basic-helix-loop-helix genes Ms23, Ms32, bHLH122, and bHLH51 in maize (Zea mays) established that male fertility requires all four genes, expressed sequentially in the tapetum. Not only do they regulate each other, but they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 84 publications
6
29
0
Order By: Relevance
“…The functions of bHLH transcription factors have been reported in animals and plants, including control of cell proliferation and specific cell lineages development (Heim et al, 2003; Toledo-Ortiz et al, 2003; Pillitteri et al, 2007; Pires and Dolan, 2010; Girin et al, 2011; Zhang et al, 2018; Zhang et al, 2021; Nan et al, 2022). Spur as a specific adjacent tissue, the pattern of cell division and cell lineages are different from the blade in Aquilegia (Shan et al, 2019; Yant et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The functions of bHLH transcription factors have been reported in animals and plants, including control of cell proliferation and specific cell lineages development (Heim et al, 2003; Toledo-Ortiz et al, 2003; Pillitteri et al, 2007; Pires and Dolan, 2010; Girin et al, 2011; Zhang et al, 2018; Zhang et al, 2021; Nan et al, 2022). Spur as a specific adjacent tissue, the pattern of cell division and cell lineages are different from the blade in Aquilegia (Shan et al, 2019; Yant et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that 15 new GMS genes have recently been identified and validated using the CRISPR/Cas9 system [ 68 , 150 , 151 ], showing the power of gene editing technologies in maize genomics and breeding. Here, a molecular regulatory network for maize male fertility is summarized and updated by considering the functional properties and sequential expression patterns of the reported maize GMS genes ( Figure 5 ).…”
Section: The Cloned Maize Gms Genes and Their Roles In Anther And Pol...mentioning
confidence: 99%
“…Although the corresponding TFs (ZmMS32, ZmMS9, ZmbHLH51, ZmMYB80 and ZmMS7) are found to be encoded by GMS genes, whether a similar genetic pathway and regulatory network exist in maize needs to be investigated. Nan et al [ 68 , 150 , 151 ] compared the mutant phenotypes of four bHLH genes, i.e., ZmMs32 , ZmbHLH51 , ZmMs23 and ZmbHLH122 , and found that all four bhlh mutants have an aberrant tapetum. Combining several recent studies, a more complicated cascade of bHLH-regulated pathways was established ( Figure 5 ) [ 68 , 151 , 155 , 159 ].…”
Section: The Cloned Maize Gms Genes and Their Roles In Anther And Pol...mentioning
confidence: 99%
See 2 more Smart Citations